2019
DOI: 10.2478/plc-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Stance-taking in Spanish-speaking Preschoolers’ Argumentative Interaction

Abstract: The aim of this study is to determine what linguistic resources are used for stance-taking in confrontational interactions. For this purpose, we analyze 70 argumentative sequences in spontaneous peer conversations during play situations of 4 dyads (2 mid and 2 low socio-economic status backgrounds) of 4 to 7-year-old Argentinian children. Stance-taking relies on the use of evaluative language, understood as the markers of speaker’s attitude (reference to internal states such as attribute, cognition, emotion, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
0
3
0
8
Order By: Relevance
“…A no- 2017) monologic-dialogic dimension, we note a near-exclusive reliance on the dialogic view of argumentation. In most studies, this was made explicitly clear in the way study authors presented their theoretical and analytical grounding, including studies that drew on discursive approaches to argumentation (e.g., Arendt, 2019;Ehrlich, 2019;Hannken-Illjes & Bose, 2018Shiro et al, 2019) as well as studies that pursued structural ends in line with established dialogic theories of argumentation, such as pragma-dialectics (e.g., Bova, 2015a-c;Bova & Arcidiacono, 2013b, 2018Convertini, 2021a,b;. However, the sample also comprises studies, where the dialogic view was not explicitly thematized or laid out.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A no- 2017) monologic-dialogic dimension, we note a near-exclusive reliance on the dialogic view of argumentation. In most studies, this was made explicitly clear in the way study authors presented their theoretical and analytical grounding, including studies that drew on discursive approaches to argumentation (e.g., Arendt, 2019;Ehrlich, 2019;Hannken-Illjes & Bose, 2018Shiro et al, 2019) as well as studies that pursued structural ends in line with established dialogic theories of argumentation, such as pragma-dialectics (e.g., Bova, 2015a-c;Bova & Arcidiacono, 2013b, 2018Convertini, 2021a,b;. However, the sample also comprises studies, where the dialogic view was not explicitly thematized or laid out.…”
Section: Main Findingsmentioning
confidence: 99%
“…Bova & Arcidiacono's (2013a) study on children's why questions in child-adult discourse shows that these serve mostly explanatory rather than argumentative purposes. Investigating children's use of evaluative and evidential language markers in their stance-taking in peer confrontational discourse, Shiro et al (2019) found a high occurrence of references to intention and obligation, in the latter case expressed through the use of various deontic expressions, as well as a high degree of assertiveness expressed by the children through negative polarity.…”
Section: Structural-discursive Featuresmentioning
confidence: 99%
“…Para los fines de este estudio, consideramos la argumentación como una práctica dialógica que depende del contexto situacional en el que ocurre (Shiro et al, 2019). Siguiendo la definición de Zadunaisky Ehrlich & Blum-Kulka (2010), se trata de una práctica social en la que las dos partes toman posiciones alternas sobre el mismo tópico y manifiestan sus posiciones adversas de diferentes maneras.…”
Section: La Argumentación Infantilunclassified
“…Siguiendo la definición de Zadunaisky Ehrlich & Blum-Kulka (2010), se trata de una práctica social en la que las dos partes toman posiciones alternas sobre el mismo tópico y manifiestan sus posiciones adversas de diferentes maneras. En el marco de esta perspectiva interactiva de la argumentación (Zadunaisky Ehrlich & Blum-Kulka, 2010;Shiro et al, 2019), los estudios han atendido a las estrategias argumentativas que emplean los niños en las disputas que mantienen tanto con adultos como con otros niños. Los estudios centrados en las interacciones con adultos describieron cómo éstos últimos colaboran con los niños en la construcción de argumentos (Castelain et al, 2018;Eisenberg, 1987).…”
Section: La Argumentación Infantilunclassified
See 1 more Smart Citation